Transition finance and its relationship to green finance - Jacob Baylon Schumacher (EconPol Forum, 2023)
Both green and transition finance aim to promote improvements to environmental outcomes of organizations. Transition finance is best defined as financial activities that are conditional on entities achieving contextually relevant environmental and socially sustainable criteria within a limited time frame. In contrast to green finance, transition finance recognizes the importance of addressing social issues along with environmental issues. Policymakers should focus on making greenwashing within transition finance and green finance more costly. As societies begin to seriously speed green transition plans, the role of transition finance will continue to grow
Keywords: 330